Could primary chemoradiotherapy in T2 glottic cancers yield results comparable to primary radiotherapy in T1?: considerations from 531 German early stage patients - Dyckhoff, Gerhard; Warta, Rolf; Herold-Mende, Christel; Rudolph, Elisabeth; Plinkert, Peter K.; Ramroth, Heribert (Cancers, 2021)
T1 glottic cancer is a highly treatable disease with local control (LC) rates over 90% by either primary radiotherapy (pRT) or transoral laser microsurgery (TLM). LC of T2 glottic cancers is 15 percent points poorer on average. However, salvage after pRT entails more than 50% total laryngectomy. Therefore, there is a need for enhanced LC. Altered fractionation regimens improved LC in T1 but not in T2. For this reason, for T2, alternative strategies must be considered. In a large observational cohort study including 531 early-stage laryngeal cancers, a small number of patients were treated with primary chemoradiotherapy (pCRT). In multivariable analysis, factors associated with significantly poorer outcomes included age, comorbidities, supraglottic localization, and T category. While there was a significant difference between pRT and surgery (HR 1.79; 95%-CI: 1.15-2.79), there was none between pCRT and surgery (HR 0.70; 95%-CI: 0.33-1.51). There is evidence from the literature that pCRT in early glottic cancers could yield results that surpass the limits so far experienced in radiotherapy alone with acceptable toxicity. Thus, prospective randomized studies with larger numbers of patients are warranted.
Gesehen am 16.06.2021